Challenges in The Implementation of Regulations in The Drafting of Cooperative Deeds in Manado - Tampi, Celline Gabrielle; Endrawati, Lucky; Sri Kusumadewi, Amelia (NEGREI: Academic Journal of Law and Governance, 2024)
This research examines the legal and practical challenges faced by notaries in the process of drafting and approving cooperative establishment deeds in Manado. The study highlights the importance of notaries in providing legal certainty for cooperatives, yet identifies significant gaps in the legal framework governing their authority. Using an empirical approach, data were collected through interviews and observations, revealing issues such as lack of standardized deed formats and insufficient coordination with relevant authorities. The findings suggest that these obstacles not only delay the establishment process but also undermine the credibility of cooperatives as legal entities. The study concludes with recommendations for improving notarial services and ensuring that cooperatives can be established with greater efficiency and legal security.